The Influence of Job Training, Job Safety and Job Satisfaction on Employees’ Performance of PT. Adhi Jaya Teknik - Setyawarni, Idah; Cik, Ahmad; Digdowiseiso, Kumba (Equivalent: Jurnal Ilmiah Sosial Teknik, 2024)
This research aims to analyze how much influence job training, job safety and job satisfaction have on the performance of PT. Adhi Jaya Teknik Jakarta employees. Data were analyzed using descriptive analysis methods and inferential analysis assisted by using the Statistical Product and Service Solution (SPSS) Version 23.0 program. The data used is primary data sourced from the results of questionnaires by respondents. The research results show that there is a positive and significant influence between job training, job safety and job satisfaction on the performance of PT Adhi Jaya Teknik employees shows that the better the job training, job safety and job satisfaction, the higher the level of employee performance. Based on the results of this research, PT. Adhi Jaya Teknik improves employee performance by paying attention to job training, job safety and job satisfaction.